Detoksikasi Air Buangan Yang Mengandung Pestisida - Siti N T Hidayati (Balai Besar Kimia dan Kemasan, 1987)
Detoxication is the transformation of a toxic substance into a less toxic product. Detoxication of the pesticide contaminated waste water can be done by biota and abiota. Detoxication by biota may involve one or more the following reactions : oxidations, dechlorinations, reductions, hydrolysis, aromatic ring cleavage, etc. Detoxication by abiota may involved physical and chemical treatment. Three types of pesticide contaminated waste water were prepared in theis experiment. The first type contain MIPC, the second Carbofuran and the other BPMC. The concentration of each type are carried out after 1,2,3, and 4 weeks. The result indicate that the longer detoxication time is better result, the kind of toxicants affected detoxication product, KOH is stronger than NaOH.